Resíduos sólidos gerados no centro de lançamento de Alcântara - Maranhão: proposta para um plano de gerenciamento de resíduos sólidos (PGRS) - SANTOS, Jorge Luis Bulcão (2021)
Excessive and disorderly generation has been a constant problem and needs to be controlled in different sectors of society. It is necessary to find solutions that can reduce the use of raw materials and minimize the impact and environmental contamination caused by inappropriate waste disposal. One of the ways to solve problems related to solid waste is its management and management. However, Solid Waste Management faces difficulties regarding its implementation and maintenance, both in companies and in public bodies. Military Organizations as bodies of the Federal Public Administration, which generate waste, must guide their actions, seeking to institute, in their routine activities, good environmental management practices, observing the legislation in force. This study aimed to carry out a survey, evaluation and analysis of the generation, segregation, collection, transport and final destination of waste generated at the Alcântara Launch Center (CLA), where important activities of the Brazilian Space Program are carried out, such as the ” Microgravity Program” when scientific and technological experiments are launched on board vehicles that reach a microgravity environment and provide data for the improvement of research in the areas of engineering, biotechnology, among others. A detailed proposal for a Solid Waste Management Plan for the CLA is presented. The methodology applied was a case study based on documents, direct observation, and data research, carrying out a survey of types, classification, quantification, generation sites and forms of collection and final disposal of waste, verifying if, thus, all the necessary aspects for the implementation of the steps foreseen in Law 12,305/2010 that institutes the National Solid Waste Policy in the Solid Waste Management Plan. It is also noteworthy that the proposed PGRS meets the goals of the Sustainable Development Goals (SDGs), established by the General Assembly of the United Nations, namely: Goal 3 - Good Health and Well-Being of the population, as it avoids disease vectors, caused by incorrect disposal of hazardous waste; Goal 11 - Sustainable Cities and Communities, taking into account the reduction of physical spaces destined to the inadequate disposal of solid waste, and Goal 12 - Responsible Consumption and Production, considering the minimization of raw materials and the reuse of materials.